Potentiating T cell tumor targeting using a combination of TCR with a Siglec-7 based CSR - Didi-Zurinam, Shiran; Katzman, Erel; Cohen, Cyrille J. (Frontiers in Immunology, 2025)
IntroductionTumors may utilize different strategies to escape T cell immunosurveillance. Besides the overexpression of checkpoint ligands (such as PDL1) or the secretion of immunosuppressive agents, several studies have shown that cancer aberrant sialylation can, through interaction with selected receptors such as those from the Siglec family, neutralize NK and T cell function.MethodsHerein, we wanted to take advantage of the presence of inhibitory sialic acid ligands on the tumor cell surface to enhance T cell anti-tumor activity. To this end, we devised a novel chimeric receptor consisting of the extracellular portion of Siglec-7 and the intracellular portion of 41BB, which can convert inhibitory signals into stimulatory ones when expressed in human T-cells.ResultsThis co-stimulatory chimeric switch receptor (CSR), when co-expressed with a tumor-specific TCR, facilitated higher cytokine secretion and activation profiles following co-culture with tumor cells. Additionally, T cells equipped with Siglec-7 CSR demonstrated improved anti-tumor function in vivo.DiscussionGiven the broad expression pattern of Siglec-7 ligands on tumor cells, our data suggest this CSR may act as a general adjuvant to boost TCR T cell function. Overall, this work provides an approach to improve engineered T-cell-based cancer treatment.